The supply and distribution of private housing (2001-2007) its effects on the urban pattern of mega Manila - Morales-Mercado, Gregoria Serra (College of Architecture, University of the Philippines Diliman, 2008)
The purpose of this study is to describe the supply and distribution of housing done by private developers in the Mega Manila region within the seven years of the Arroyo administration (2001-2007). It is assumed that the government policies and market forces create a favourable economic climate for the activities of private developers to be encouraged. The supply and distribution of the government thrust in challenging private participation as the solution to the housing problem is also discussed. The findings are geared to challenge government and private sectors to rethink their strategies in moving towards the solution of the housing and urbanization problems in Mega Manila.